2014
DOI: 10.3354/ab00545
|View full text |Cite
|
Sign up to set email alerts
|

Intraspecific variation in carapace morphology among fiddler crabs (Genus Uca) from the Atlantic coast of Brazil

Abstract: Isolation due to geographical barriers should promote genetic and morphological divergence among populations. Marine currents flowing in opposing directions along landmasses can constitute barriers that isolate populations dependent upon aquatic dispersal. The distribution of fiddler crabs (genus Uca) is regulated primarily by the oceanic transport of their planktonic larvae and by available adult habitat. Along the Brazilian coast of eastern South America, the flow of 2 major oceanic currents separates northe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 61 publications
2
25
0
3
Order By: Relevance
“…Another example of phenotypic plasticity in the carapace shape of fiddler crabs was reported by HAMPTON et al (2014), who found a significant morphological divergence in the carapace (variations in the hepatic or branchial regions) among the northern and southern populations of eight species living along Brazilian coast (between Amapá and Santa Catarina States). These authors attributed this divergence to the existence of a geographic barrier (Central South Equatorial Current that splits into two circulation patterns, North Brazil and South Brazil Current) for the et al (2013) larval planktonic stage of these species.…”
Section: Discussionmentioning
confidence: 99%
“…Another example of phenotypic plasticity in the carapace shape of fiddler crabs was reported by HAMPTON et al (2014), who found a significant morphological divergence in the carapace (variations in the hepatic or branchial regions) among the northern and southern populations of eight species living along Brazilian coast (between Amapá and Santa Catarina States). These authors attributed this divergence to the existence of a geographic barrier (Central South Equatorial Current that splits into two circulation patterns, North Brazil and South Brazil Current) for the et al (2013) larval planktonic stage of these species.…”
Section: Discussionmentioning
confidence: 99%
“…From the results obtained in this study, it cannot be inferred at this point that the Amazon river functions as a barrier to gene flow in the two studied fiddler crabs. Yet, although Wieman et al [39] did not find evidence for significant genetic distinction, theyas well as Hampton et al [40]. detected significant morphometric differentiation that may hint at speciation commencement or phenotypic plasticity as response to ecological parameters [57].…”
Section: Discussionmentioning
confidence: 99%
“…some Jamaican individuals were much larger and had different coloration), although not yet statistically analyzed. Thus, statistical analyses on morphology are highly encouraged, including both morphometrics and trophic morphology to elucidate possible ecological adaptations and/or phenotypic plasticity as for example found in cave living crabs [82], as well as in other fiddler crabs [39, 40, 47]. Habitat variations within a broad distributional range that are not sufficiently large when related to effective dispersal, more likely result in phenotypic plasticity rather than actual local adaptation [83].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Shih et al (2016) reviewed the taxonomy of the genus and recognized all subgenera of Uca as full genera based on molecular evidence. Ten species are found in Brazil, including Studies on M. mordax have been carried out on various aspects: description of the developmental stages; density; relative growth; population dynamics and intraspecific variation (Rieger, 1997;Masunari & Dissenha, 2005;Masunari, 2006;Fransozo et al, 2009;Thurman et al, 2013;Hampton et al, 2014). However, no study on the morphology of the juvenile phase of this species has been previously undertaken.…”
Section: Introductionmentioning
confidence: 99%